2017
DOI: 10.1177/2332858416683649
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Loan Aversion in Education

Abstract: As the college-going population becomes increasingly diverse and the cost of college continues to rise, it is critical that we better understand the underlying mechanisms by which prospective students make decisions about whether and how to finance their education beyond high school. Student loans are an increasingly necessary tool to help students pay for postsecondary education. Though 35% of all undergraduate students and 55% of all graduate students receive some type of federal loan to help finance their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(30 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…Research on Latinx experiences with student loans emphasizes their aversion to borrowing (Boatman et al, 2017). This is problematic given that non-borrowing Latinx students have been less likely to attain their degrees (Cunningham & Santiago, 2008).…”
Section: Latinx Student Loan Aversionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research on Latinx experiences with student loans emphasizes their aversion to borrowing (Boatman et al, 2017). This is problematic given that non-borrowing Latinx students have been less likely to attain their degrees (Cunningham & Santiago, 2008).…”
Section: Latinx Student Loan Aversionmentioning
confidence: 99%
“…This is problematic given that non-borrowing Latinx students have been less likely to attain their degrees (Cunningham & Santiago, 2008). Boatman et al (2017) also suggested that avoiding borrowing is more dependent on context. They noted that family influence plays a major role in Latinx decisions to borrow, and speculated that Latinx students were more averse to borrowing because of having less familial capital than their White peers (Boatman et al, 2017).…”
Section: Latinx Student Loan Aversionmentioning
confidence: 99%
See 1 more Smart Citation
“…High college costs, both perceived and actual, can have important effects on students' decisions whether to attend college and, if so, which college to attend (Dynarski, Libassi, Michelmore, & Owen, 2018). The prospect of needing to borrow can even deter some students' participation in higher education altogether (Boatman, Evans, & Soliz, 2017). Identifying why and how borrowing has increased over time is paramount to understanding how students participate and succeed in higher education.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With respect to student loans, the most common argument made in its favour is that students from poor households are not able to enrol themselves in higher education due to their financial problems; and educational loan enables them to pursue higher education by deferring the current costs and to pay the same in future when they have secure jobs. But available evidence (e.g., Boatman et al 2017;Callender and Mason 2017) also shows that prospective undergraduates especially from low social and economic classes feel deterred from applying to university education because of fear of debt.…”
Section: Introductionmentioning
confidence: 99%